Bulky countercation effects on the crystal packing of anionic dithiooxalato-containing Ni(ii), Pd(ii) and Pt(ii) complexes: spectroscopic–redox correlations. Issue 26 (20th June 2022) - El Alouani Dahmouni, Nadia; Switlicka, Anna; Machura, Barbara; Moliner, Nicolás; Rabelo, Renato; Ruiz-García, Rafael; Stiriba, Salah-Eddine; Cano, Joan; Julve, Miguel
Abstract : The metal ion, countercation and crystallization solvent control the packing of bis(dithiooxalato- k 2 S, S′ )metallate(ii ) complex anions in the solid state. Abstract : Herein, we report the synthesis, X-ray structures, thermal stability, spectroscopic characterization and redox properties of compounds of formulas (BzPh3 P)2 [Ni(dto)2 ] (1 ), (BzPh3 P)2 [Pd(dto)2 ]· n CH2 Cl2 [ n = 0 (2 ) and 3 (2 ·3CH2 Cl2 )], (BzPh3 P)2 [Pt(dto)2 ] (3 ), (Ph4 As)2 [Ni(dto)2 ]· n (CH3 )2 CO [ n = 0 (4 ) and 1 (4 ·(CH3 )2 CO)], (Ph4 As)2 [Pd(dto)2 ] (5 ) and (Ph4 As)2 [Pt(dto)2 ] (6 ) (dto 2− = dithiooxalate, BzPh3 P + = benzyltriphenylphosphonium and Ph4 As + = tetraphenylarsonium), together with the synthesis and X-ray structure of the corresponding diphenyl dithioxalate proligand (Ph2 dto). The crystal structures of 1–6 and those of the solvated compounds 2 ·3CH2 Cl2 and 4 ·Me2 CO have in common the presence of discrete planar [M(dto)2 ] 2− complex anions where the divalent metal ions exhibit rectangular (M = Ni) or quasi square planar MS4 (M = Pd and Pt) environments. The M–S bond lengths are typical of n d 8 M II ions [ n = 3 (Ni), 4 (Pd) and 5 (Pt)] in a low-spin (LS) electronic configuration, varying in the order 2.17 (Ni) < 2.30 (Pd) ≈ 2.29 Å (Pt). The electroneutrality is achieved by bulky BzPh3 P + (1–3 and 2 ·3CH2 Cl2 ) and Ph4 As + [4–6 and 4 ·(CH3 )2 CO] countercations. Segregated (1–3 and 4–6 ) or mixed [2 ·3CH2 Cl2 and 4 ·(CH3 )2 CO] layers of complex anions and cations linked by electrostatic forces and Van der Waals interactions together with very weak S⋯OC and C–H⋯OC type contacts occur in them. The dichloromethane and acetone molecules of crystallization occupy the interlayer space or are embedded within the mixed layers, respectively. The redox chemistry of the [M(dto)2 ] 2− complex anions of 4–6 was investigated by cyclic voltammetry in acetonitrile solution. The one-electron metal centred irreversible oxidations were evident in the cyclic voltammograms with oxidation potentials of +0.18 (Ni), +0.72 (Pd) and +0.45 V (Pt) vs. Fc + /Fc. The UV-vis spectra of acetonitrile solutions of the square planar [M(dto)2 ] 2− species of 4–6 are similar, and they show a broad, intense metal-to-ligand charge transfer (MLCT) transition centred at 498 (Ni), 376 (Pd) and 422 nm (Pt). A linear correlation between the values of energy of the MLCT transition and those of the formal redox potential is found along this [M II (dto)2 ] 2− family pointing out an important contribution from a n d– n d ( n = 3–5) transition.